Lymphocytes subsets reference values in childhood. (6th August 2014) - Tosato, F.; Bucciol, G.; Pantano, G.; Putti, M. C.; Sanzari, M.C.; Basso, G.; Plebani, M.
Abstract Immunophenotyping of blood lymphocyte subsets and activation markers is a basic tool in the diagnostic process of primary immunodeficiency diseases, its use becoming more and more widespread as the knowledge about these illnesses increases. However, the availability of reliable reference values, which need to be age‐matched for the pediatric population, is a pre‐requisite for the reliable interpretation of immunophenotyping data. Aim of this study is to analyze the lymphocyte subsets and activation markers distribution in children aged 0–18 years referring to the University Hospital of Padova and to create age‐matched reference values expressed by percentiles, thus providing a valuable guideline for the interpretation of the immunophenotype. © 2014 International Society for Advancement of Cytometry